Keberkesanan Kaedah "Accelerated Learning" Dalam Pembelajaran Fizik Kbsm. - Che Mat, Che Soh (1994)
Accelerated learning is one of the methodology in the Integrative learning system, which is said to be brain compatible and uses multiple intelligence. The accelerated learning method is based on the theory developed by Georgi Lozanov. The effectiveness of this method is found to be encouraging in the learning of second language